Private food standard certification: analysis of the BRC standard in Italian agri-food. Issue 1 (6th January 2014) - Spadoni, Roberta; Lombardi, Pamela; Canavari, Maurizio; Hingley, Martin
Abstract : Purpose: – The aim of this paper is to assess the applicability and impact of private food standards – specifically that of the BRC (British Retail Consortium) – in a European country context, and to classify food companies into groups on the basis of their different perceptions regarding the Global Standard for Food safety impacts. Design/methodology/approach: – The research is developed in two stages: a qualitative investigation based on in-depth interviews with quality managers (QMs); a quantitative investigation with a structured questionnaire: with response from 192 food processors in Italy, selected through a probabilistic random sampling method. Data were elaborated with descriptive statistical techniques and subsequently with multivariate analysis (factor and cluster analysis). Findings: – QMs agree with most of the assumptions with regard to the impact elements of the BRC food standard. Some characteristics, such as geographic location, size, and type of processing and adoption of ISO 9001, seem to elicit different perceptions between the companies. Through factor analysis, eight factors were extracted; and subsequently, through cluster analysis applied to the factors, five different groups of companies are identified. Practical implications: – The adoption of private food standards is both useful and comprehensible for food operators. However, BRC is a minimum standard and a base level for food suppliers; it cannot wholly substitute a specific retailer's dedicated second-party audit. Findings could be used by the subjects of the certification process to determine ideal marketing strategies. Originality/value: – This paper provides a statistically significant description of the impact of private food standards (via the important BRC standard) in one of the most important European markets.